THE COMPREHENSIVE APPROACH IN NATIONAL RECONSTRUCTION OF STATES AND LEGITIMATE SECURITY: LA LEGÍTIMA SEGURIDAD (Journal of the Spanish Institute for Strategic Studies, 2018)
The two best examples of the implementation of the concept of the“comprehensive approach” to nation-building operations are those ofthe international community’s participation in Iraq and Afghanistan,both under the relevant legal endorsement of the United Nations. Consideringthe results obtained in each of the countries, with the conclusionof the security sector reform phase in the former (and with thelatter going through its final consultancy phase and mentoring period),it is now time to question whether the lessons learned have been thecorrect ones or whether there is a need to rethink these operations,particularly those relating to security and governance.